Giant Spermatocele Mimicking Hydrocele: A Case Report - Hsin-Chih Yeh; Chii-Jye Wang; Chia-Chu Liu; Wen-Jeng Wu; Yii-Her Chou; Chun-Hsiung Huang (Kaohsiung Journal of Medical Sciences, 2007)
Spermatoceles are usually asymptomatic and often found incidentally during physical examination. We report a case of giant spermatocele that mimicked a hydrocele. A 55-year-old man suffered from right scrotal enlargement for several years. As the heavy sensation and scrotal soreness worsened in recent months, he came to our outpatient clinic for help. Hydrocele was suspected due to transilluminating appearance of the scrotal content. Surgical exploration was arranged and a giant spermatocele was found. Total excision of the spermatocele was performed and the patient recovered well. The specimen was sent for pathology and spermatocele with spermatozoa was noted.